In vitro activity of tigecycline against Acinetobacter baumannii isolates from a teaching hospital in Malaysia - Dhabaan, G.N.; AbuBakar, Sazaly; Shorman, M.A.; Hassan, H. (2012)
The In vitro susceptibility of clinical and environmental isolates of Acinetobacter baumannii to tigecycline and other antibiotics was determined by disk diffusion method. The E-test was used to determine the minimum inhibitory concentration (MIC). The growth curves of tigecycline treated environmental and clinical strains were established. Fifty-seven percent and 75 of the clinical and environmental isolates were MDR strains, respectively. Ninety-five percent of the clinical isolates were susceptible to tigecycline and 5 showed intermediate resistance with MIC ranging between 0Â·032 and 3 mg/l. Tigecycline susceptible and intermediate resistance among the environmental isolates were 40 and 60, respectively, with a significantly lower MIC range of 0Â·5â4 mg/l. The bacterial growth curves demonstrated the higher ability of the environmental strains to tolerate the antibiotic effects than the clinical strains. The relatively high resistance profile among the environmental isolate suggests an insidious emergence of tigecycline resistance amongst A. baumannii. Strict infection control procedures are imperative to prevent the dissemination of tigecycline-resistant A. baumannii strains in the hospital environment.